Carbon‐Atom Extrusion from Halobenzenes and Its Coupling with a Methylene Ligand to Form Acetylene. Issue 27 (3rd June 2015) - Zhou, Shaodong; Schlangen, Maria; Li, Jilai; Wu, Xiao‐Nan; Schwarz, Helmut
Abstract Mechanistic aspects of an unusual gas‐phase reaction of [LaCH2]+ with halobenzenes have been investigated using Fourier‐transform ion cyclotron resonance (FTICR) mass spectrometry combined with density functional theory (DFT) calculations. In this thermal process a carbon‐atom from the benzene ring, most likely the ipso‐position, and the carbene ligand are coupled to form C2H2.